An Environmental‐Economic Analysis of a Case Solar Power Plant for Power Decarbonization - Seyedeh Hosna Talebian; Hossein Balouchi; Danial Esazadeh; Mahsa Abbasi; Hamidreza Azizi (Energy Science & Engineering, 2025)
ABSTRACT On the path to achieving net‐zero emissions targets by 2050 and meeting the increasing electricity demand, investigations on the carbon intensity of electricity is of interest as an important decision‐making parameter in decarbonizing the power sector and replacing nonrenewable power plants in regions of low rainfall and limited water resources to enhance the transparency of policies toward net‐zero transition. In this context, the potential of solar photovoltaics (PV) has been highlighted in recent years due to their low‐emission intensity compared to other renewable sources, highly regarded economic prospects, and unprecedented global growth of installations. Considering Iran's power crisis in terms of the mismatch between production and consumption and a worsening of the environment due to high‐carbon power, this paper presents the assessment of the environmental and economic viability of a 10 MW on‐grid solar PV plant to improve energy security and sustainability. First, the carbon intensity (CI) and levelized cost of energy (LCOE) of electricity generated in the power industry in Iran in comparison with the global status is discussed. Then, the environmental aspects of different types of PV inverter modulus and panels are assessed by utilizing the life cycle assessment approach, to select the optimum design in terms of CI. Finally, the economic scenarios are analyzed in terms of LCOE and the sensitivity analysis on the availability factor. The combined environmental‐economic assessment results of the case solar power plant with CI of 63.9 tCO2/GWh and LCOE of 11 $/MWh offers deep insights into the financial and environmental performance of solar PVs in the country's sustainable development roadmap and highlights the importance of regulatory policies, absorbing green climate funds, and investment in the expansion of solar systems to enable the decarbonization of electricity as an important measure for sustainable development.